The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3922/j.psns.2014.037
|View full text |Cite
|
Sign up to set email alerts
|

Humans tend to walk in circles as directed by memorized visual locations at large distances.

Abstract: Human veering while walking blindfolded or walking straight without any visual cues has been widely studied over the last 100 years, but the results are still controversial. The present study attempted to describe and understand the human ability to maintain the direction of a trajectory while walking without visual or audio cues with reference to a proposed mathematical model and using data collected by a global positioning system (GPS). Fifteen right-handed people of both genders, aged 18-30 years, walked wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…However, there was no significant difference in preference for right and left orientation when considering the overall trials, but substantial within-subject variability and between-subject variability from trial to trial were observed (Bestaven et al, 2012). The findings of the previous three studies have been corroborated by the findings of a very recent study that examined veering behavior in right-handed humans but under different experimental conditions (Consolo, Holanda, & Fukusima, 2014), In this study, participants were allowed to see the target for a brief period of time, then blindfolded, and asked to walk without any visual or auditory cues in an open field directly toward the target. This study demonstrated that irrespective the target distance, the most frequently used pattern was the circular trajectory.…”
Section: Directionality Bias In Turning or Rotational Behaviorsupporting
confidence: 70%
See 1 more Smart Citation
“…However, there was no significant difference in preference for right and left orientation when considering the overall trials, but substantial within-subject variability and between-subject variability from trial to trial were observed (Bestaven et al, 2012). The findings of the previous three studies have been corroborated by the findings of a very recent study that examined veering behavior in right-handed humans but under different experimental conditions (Consolo, Holanda, & Fukusima, 2014), In this study, participants were allowed to see the target for a brief period of time, then blindfolded, and asked to walk without any visual or auditory cues in an open field directly toward the target. This study demonstrated that irrespective the target distance, the most frequently used pattern was the circular trajectory.…”
Section: Directionality Bias In Turning or Rotational Behaviorsupporting
confidence: 70%
“…In such a situation people probably find themselves rendered helpless, which cause them either to stay (if not asked to walk/move) or to walk/move (if asked to do) in circles around their current standing positions (possibly within a short range of distance) rather than getting lost by walking toward an uncertain distant goal or target. However, researchers have suggested that this nature of veering can be caused by vestibular function (Consolo et al, 2014) rather than DA imbalance in the brain (Mohr & Lievesley, 2007). …”
Section: Directionality Bias In Turning or Rotational Behaviormentioning
confidence: 99%
“…When executing a goal-directed trajectory in the absence of landmarks, humans rely on path integration (the integration of self-motion cues to determine the position and heading) and an internal representation of the environment [9, 33]. However, path-integration without the correction from external directional references is prone to accumulating noise resulting in increasing positional and heading errors throughout the trajectory [13, 56] (see Figure 2A). Similarly, noise in observation (see Figure 2B) and representation (see Figure 2C) lead to variability in endpoints even in the absence of errors caused by noisy motor actions.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond being able to capture and explain empirical data from multiple triangle completion tasks, including behavior considered contradictory under ideal observer models, the dynamic Bayesian actor model allows to reconcile previous accounts of navigation in a coherent computational framework. The present model includes perception [8], representation [33], planning [65] and execution of motor actions [12,13,56], while considering uncertainty, which allows predicting and explaining how these seemingly separate processes interact in producing observed navigation behavior in triangle completion task. The homing task with landmarks has been described as comprising several different 'navigational strategies' while the task unfolds.…”
Section: Relation To Other Experimental Workmentioning
confidence: 99%
“…However, poor correlations exist between leg length difference, handedness, or lateral preference, while head posture increases the error [ 2 4 ]. This suggests a role for the neck proprioceptive or vestibular input in stabilizing the stepping orientation [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%